Impacto dos fatores de interação homem-máquina no Enterprise Resource Planning (ERP) software design - Ozen, Cagla; Basoglu, Nuri; Daim, Tugrul (Revista de Administração da UFSM, 2009)
Enterprise Resource Planning (ERP) systems integrate processes and functions across the company by using a single data repository. Today ERP systems are not only accepted as simple software packages but a core engine of a framework for business processes. Since adopters of ERP systems have a great number of alternatives during the selection process, software vendors should differentiate their product. Various differentiation policies can be applied by software vendors to achieve competitive advantage in the market. This paper is focusing on one of these policies; area of man-machine interaction. In this study, first, adaptive and intelligent characteristics for the user interface of the ERP package were explored by conducting survey to ERP system end-users. In this survey, we primarily aim to understand and model the factors that are affecting end-user satisfaction with the ERP system and its interface design. The results indicate that ease of use (EoU) and usefulness are determinants of end-user satisfaction with ERP system and its interface design. This paper discusses these findings, the models that we were inspired while we had been forming our model, our model framework and finally describes future study opportunities about human and computer interaction analysis and prototyping studies in ERP systems.